Suitability of the clonal marbled crayfish for biogerontological research: a review and perspective, with remarks on some further crustaceans - Vogt, Günter (Biogerontology, 2010)
This article examines the suitability of the parthenogenetic marbled crayfish for research on ageing and longevity.
Gesehen am 12.09.2023